Analysis of efficiency of application of media with hyaluronic acid in cryoprotocols - Natalia V. Protopopova; Elena B. Druzhinina; Kseniia V. Krylova; Iuliia V. Mylnikova; Jan A. Dvoryanov; Albina V. Labygina; Inna I. Kovalenko (IP Berlin A.V., 2020)
According to the World Health Organization, about 2 million new couples experience infertility annually, and their number is growing. An effective way to overcome infertility is assisted reproductive technology (ART). Cryopreservation will rationally solve the issue of preservation and further use of embryos: to delay pregnancy for some time considering womans desire and to prevent ovarian hyperstimulation syndrome. Embryo freezing allows to reduce the rate of repeated ovarian stimulation and perform preimplantation genetic diagnosis. Over the past decades, various cryotransfer options have been proposed to increase ART treatment efficacy, including the use of a culture medium with a high concentration of hyaluronic acid, but there are conflicting data on the use of such a medium in ART programs. Aim. Evaluation of thawed embryo transfers efficacy using the hyaluronic acid-containing culture medium. To achieve the goal, the following tasks were set: to evaluate clinical and medical history data of patients with tubal infertility in cryoprotocols, to analyze the previous cycle of in vitro fertilization and embryological stage, to evaluate the effectiveness of the culture medium with a high content of hyaluronic acid. Materials and methods. A detailed description of the patient sample, inclusion and exclusion criteria, embryological stage, embryo grading, devitrified embryo transfer technique. The article includes 3 tables which present the groups general clinical characteristics, the embryological stage, the rate of pregnancy, depending on the cultivation day. Results. The authors established that in patients with a history of pelvic surgery and sexually transmitted infections, it is advisable to use the culture medium with a high content of hyaluronic acid to transfer the thawed embryo. It was shown that pregnancy rate is 1.5 times higher when transferring devitrified embryos on the 5th day of development with the use of hyaluronic acid-containing culture medium. The conclusion about the pregnancy rate in obese patients is not indisputable, which requires further study. The authors also provide practical recommendations on the use of the culture medium with hyaluronic acid in cryoprotocols. Conclusion. The study allows to optimize the devitrified embryo transfer in patients with tubal infertility using a culture medium with a high content of hyaluronan. This work has undoubted scientific and practical significance.